The characteristics of inhalant users - Evren, Cüneyt; Ögel, Kültegin; Tamar, Defne; Çakmak, Duran (Journal of Dependence, 2001)
Objective: Inhalant abuse creates lots of problems, which increases in time, for user him/her self, for his/her environment and for the society. In this study it’s aimed to investigate the some characteristics of inhalant users.Method: The data of the 72 inhalant users, which was collected from the study that was done in 9 cities in Turkey and North Cyprus, was evaluated.Results: The mean age of the inhalant users were 19 andmean year of the education they had was 7.3. 86.2% of the subjects quit their education, 65.3% of them had physical, 56,9% of them had verbal childhood history of abuse, 44.5% had a family history of heavy alcohol use, 20.8% had a family history of dmg use. "To get away from boredom and pain" (66.7%) and "for pleasure" (63.9%) was the most frequent reasons for inhalant use. While answers that was given to some of the questions in our study showed that depressive symptoms was high, suicide rate among inhalant users was 16.7%. The number of subjects who had trouble with the law was found as 38 (52.8%).Conclusion: Prevention program for inhalant use and risk groups to whom this program will be applied, must be determined. One of the properties of this program must be for keeping the youngsters to stay in educational process and out of criminal acts. Children and adolescent who has depressive symptoms and history of alcohol and drug use in their environment and family seems to be under the risk for using inhalants.
Keywords: Turkey; inhalant; inhalant abuse